Formulation and evaluation of nanoparticulate ofloxacin ophthalmic gel using ionic gelation method (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
Oflaxacin is an ophthalmic and topical anti-bacterial agent used in the management of Allergic conjunctivitis, Trachoma, Blepharitis. The basic idea behind the development of such a system is to maintain a sustained drug release from the dosage form. Oflaxacin is suitable candidate for formulation into sustained dosage form in order to prolong the release of drug. The drug-excipient compatibility studies were carried out by using FTIR technique. Based on the results, excipients were found to be compatible with ofloxacin. In preformulation study, estimation of Ofloxacin was carried out by systronics UV spectrophotometer at λmax 284nm using distilled water, which had a good reproducibility and this method was used in entire study. Formulation was prepared by using ionic gelation method .The response drug content, entrapment efficiency, diffusion, spreadability, In vitro drug release was evaluated Drug content ranging from to 82.6 % to 91.24% entrapment efficiency values are ranged from 91.25% to 94.02% and in -vitro drug release studies are also studied. The In-vitro drug release study of Ofloxacin was carried out by using In-vitro diffusion apparatus.100ml of using tear fluid was taken in a beaker. The solution was stirred with 100rpm by maintaining the temperature of 37˚c ± 5˚c. The drug release data were explored for this type of release mechanism followed. The best fit with the highest determination R2 coefficients was shown by both the models (zero and peppas) followed by Higuchi model which indicate the drug release via diffusion mechanism. However as indicated by the values of R both of the models (zero and peppas) followed by Higuchi model were found to be efficient in describing the release of Ofloxacin.